STA-MCA Bypass as a “Bridge” to Pituitary Surgery in a Patient with an Adenoma Occluding the Internal Carotid Artery: Case Report and Review of the Literature - Luigi A. Lanterna; Carlo Brembilla; Antonio Signorelli; Paolo Gritti; Emanuele Costi; Gianluigi Dorelli; Claudio Bernucci (Case Reports in Neurological Medicine, 2015)
Occlusion of the intracranial internal carotid artery (ICA) by a pituitary adenoma with resulting cerebral ischemia is a very rare but devastating occurrence. The authors present a case in which a condition of symptomatic ICA occlusion due to a giant pituitary adenoma was successfully treated using a preliminary extraintracranial bypass as a “bridge” to the tumor removal. A 52-year-old patient presented with a minor stroke followed by pressure-dependent transient ischemic attacks consistent with a condition of hypoperfusion. MR imaging and a digital subtraction angiography revealed a pituitary adenoma occluding the ICA on the right side. He underwent a superficial temporal artery to middle cerebral artery (STA-MCA) bypass with the aim of revascularizing the ischemic hemisphere and reducing the risk of perioperative stroke or stroke evolution. The patient was subsequently operated on to remove the adenoma through a transsphenoidal approach. The postoperative course was uneventful and the patient has suffered no further ischemic events. When there are no emergency indications to decompress the optical pathways but the patient is at risk of impending stroke because of ICA occlusion, a two-step strategy consisting of a bypass and subsequent removal of the pituitary adenoma may be a valuable option.